Chronic Stroke Outcome Measures for Motor Function Intervention Trials: Expert Panel Recommendations. (October 2015) - Bushnell, Cheryl; Bettger, Janet Prvu; Cockroft, Kevin M.; Cramer, Steven C.; Edelen, Maria Orlando; Hanley, Daniel; Katzan, Irene L.; Mattke, Soeren; Nilsen, Dawn M.; Piquado, Tepring; Skidmore, Elizabeth R.; Wing, Kay; et al.
Abstract : Background—: About half of survivors with stroke experience severe and significant long-term disability. The purpose of this article is to review the state of the science and to make recommendations for measuring patient-centric outcomes in interventions for motor improvement in the chronic stroke phase. Methods and Results—: A 9-member expert panel reviewed evidence to identify measures of upper and lower extremity function used to date as outcomes in trials with patients who experienced a stroke ≥6 months before assessment. Outcome measures were screened using StrokEDGE consensus panel recommendations, and evaluated for availability of a published minimal clinically important difference. Measures meeting these criteria were further evaluated with regard to their level of measurement, psychometric properties, and ability of minimal clinically important difference to capture gains associated with improved function and clinical relevance to patients, to arrive at recommendations. A systematic literature review yielded 115 clinical trials of upper and lower extremity function in chronic stroke that used a total of 34 outcome measures. Seven of these had published minimal clinically important differences and were recommended or highly recommended by StrokEDGE. Those are the Fugl-Meyer Upper Extremity and Lower Extremity scales, Wolf Motor Function Test, Action Research Arm Test, Ten-Meter and Six-Minute Walk Tests, and the Stroke Impact Scale. All had evidence for their psychometric performance, although the strength of evidence for validity varied, especially in populations with chronic stroke Fugl-Meyer Upper and Lower Extremity scales showing the strongest evidence for validity. Conclusions—: The panel recommends that the Fugl-Meyer Upper and Lower Extremity scales be used as primary outcomes in intervention trials targeting motor function in populations with chronic stroke. The other 6 measures are recommended as secondary outcomes. Abstract : Supplemental Digital Content is available in the text.